Pilomatrix carcinoma on the left side of the parotid region: A case report and review of the literature - LIU, JI-FENG; LI, BIN; FAN, ZI-XUAN; JIAO, TING; LI, CHAO; QIN, SHENG; LANG, JIN-YI; CHEN, JIN-XIU (Oncology letters, 2015)
Pilomatrix carcinoma (PC) is a rare neoplasm, particularly in the parotid region. Thus, it is easily misdiagnosed and an optimal treatment regimen has not yet been established. The present study reports the case of a 43-year-old female who presented with a PC of the parotid region and reviews the associated published literature. The patient underwent three surgical excisions prior to the tumor being completely removed, and was misdiagnosed four times prior to the correct diagnosis. Once the tumor was completely removed, the patient received radiation therapy (RT). At the 2-year follow-up, the patient remained free of local recurrence and metastasis. To the best of our knowledge, only 3 cases of PC on the parotid region have been reported. Although an optimal treatment regimen has not been established, surgery with wide margins is recommended, with RT and chemotherapy producing mixed results.